A multilevel analysis of risk and protective factors for Canadian youth injured or killed by interpersonal violence. Issue 3 (24th July 2017) - Snider, Carolyn E; Brownell, Marni; Dufault, Brenden; Barrett, Nicole; Prior, Heather; Cochrane, Carla
Abstract : Purpose: The study's purpose was to determine individual-level and neighbourhood-level risk and protective factors for severe intentional injury among youth. Methods: We conducted a multilevel case–control study using registry data to determine individual-level and neighbourhood-level social determinants associated with severe violent injury/homicide among youth from Winnipeg, Manitoba. Results: The study includes 13 206 youth, aged 12–24 years (1222 cases, 11 984 controls). Individual-level risk predictors of being a victim of violence were male sex (OR 5.72 (95% CI 4.77 to 6.86)) and First Nations (OR 2.76 (95% CI 2.32 to 3.29)). Education was inversely associated with victimisation for individuals under (OR 0.36 (95% CI 0.26 to 0.51)) and over (OR 0.58 (95% CI 0.49 to 0.69)) 18 years. Ever having been in protective care (OR 1.66 (95% CI 1.39 to 1.99)), receiving income assistance from the government (OR 1.26 (95% CI 1.05 to 1.51)) or ever having criminal charges (OR 4.76 (95% CI 4.08 to 5.56)) were also significant predictors of being a victim of violence. Neighbourhood-level risk factors for victimisation included low socioeconomic status (OR 1.14 (95% CI 1.04 to 1.25)) and high levels of assault (OR 1.07 (95% CI 1.04 to 1.10)). Conclusions: This study demonstrates a complex web of risk and protective factors among youth injured by violence. It underscores the ongoing, injurious effects of historical trauma experienced by many Canadian First Nations people. Strong victim–perpetrator overlap suggests that intersectoral policies are needed to address these issues. Our findings highlight the need to improve education and family supports.